Association between longitudinal dietary patterns and changes in obesity: a population-based cohort study - Zheng, Liuyan; Lu, Xinyue; Guo, Jianhui; Xu, Xingyan; Yang, Le; Xie, Xiaoxu; Li, Huangyuan; Wu, Siying (Frontiers in Public Health, 2023)
Introduction Research on the trajectory of dietary patterns and changes in obesity has been inconclusive. Methods This study described the dietary intake and adiposity trajectories of Chinese adults and assessed the association between dietary trajectories and changes in body mass index (BMI) and waist-to-hip ratio (WHR). We used data from 3, 643 adults who participated in the China Health and Nutrition Survey from 1997 to 2015. Detailed dietary data were collected by conducting three consecutive 24-h recalls. Multitrajectories of diet scores were identified by a group-based multitrajectory method. We described the change in BMI and WHR using group-based trajectory modeling. We assessed the associations between dietary trajectories and changes in people with obesity using a logistic regression model. Results Our study revealed four trajectories of low-carbohydrate (LCD) and low-fat diet (LFD) scores. Three adiposity trajectories were identified according to the baseline level and developmental trend of BMI and WHR. Compared with the reference group, which was characterized by sustained healthy dietary habits with healthy diet scores at baseline and sustained maintenance of healthy diet scores, the other three diet trajectories had a higher risk of falling into the adverse adiposity trajectory. Discussion Maintaining a healthy LCD and LFD can markedly decrease the risk of adiposity.